Frequency Of Feto-Maternal Outcomes In Prelabour Rupture Of Membranes - Shahwar, Durre; Bokhari, Nadia Ahmed; Akram, Ayesha; Irshad, Samina; Fatima, Ambreen; Raza, Asia (Journal of Rawalpindi Medical College, 2025)
Objective : To determine the frequency of fetomaternal outcomes in patients with prelabour rupture of membranes presenting to tertiary care hospitals. Methods: A descriptive study was conducted at the Department of Obstetrics and Gynaecology, Fauji Foundation Hospital, Rawalpindi from 25th March 2023 to 25th January 2024 A total of 245 patients with prelabour rupture of membranes (PROM) were included in the study, fulfilling the inclusion criteria. All patients were managed as per standard protocol and followed until delivery. Data regarding fetomaternal outcomes was noted. Results: This study found that the mean age of the patients was 29.89 ± 5.83 years. Among 245 patients of PROM, in 160 cases maternal and in 90 instances fetal complications were observed. As per maternal outcomes, 93 (58%) underwent cesarean section, puerperal sepsis was observed in 31 (19%) and 36 (23%) wound site infections occurred. On the neonatal side, 29(32%) had low APGAR scores while 26 among 90 (29%) had low birth weight. NICU admission was necessary in 21 (23%) babies while fetal distress was recorded in 14 (16%) newborns. Conclusion: Our study has concluded that a considerable proportion of patients with PROM experienced fetomaternal complications. Among maternal complications, it is observed that a significant number of pregnant women with PROM required cesarean sections. This warrants a careful and timely management of such cases to ensure good fetal outcomes. Keywords: Fetal membranes, Premature rupture, Fetal distress, Puerperal infection, Cesarean section